A generic protocol for protein crystal dehydration using the HC1b humidity controller. Issue 5 (1st May 2016) - Lobley, Carina M. C.; Sandy, James; Sanchez-Weatherby, Juan; Mazzorana, Marco; Krojer, Tobias; Nowak, Radosław P.; Sorensen, Thomas L.
Abstract : A generic protocol for investigating crystal dehydration is presented and tested with a set of protein crystal systems using the HC1b high‐precision crystal humidifier/dehumidifier. Abstract : Dehydration may change the crystal lattice and affect the mosaicity, resolution and quality of X‐ray diffraction data. A dehydrating environment can be generated around a crystal in several ways with various degrees of precision and complexity. This study uses a high‐precision crystal humidifier/dehumidifier to provide an airstream of known relative humidity in which the crystals are mounted: a precise yet hassle‐free approach to altering crystal hydration. A protocol is introduced to assess the impact of crystal dehydration systematically applied to nine experimental crystal systems. In one case, that of glucose isomerase, dehydration triggering a change of space group from I 222 to P 21 21 2 was observed. This observation is supported by an extended study of the behaviour of the glucose isomerase crystal structure during crystal dehydration.